Practical approach to the safe use of cannabidiol in patients with refractory epilepsy: a mini review - Navarro, Cristian E. (Frontiers in Pharmacology, 2025)
Drug-resistant epilepsy (DRE), characterized by seizures that are unresponsive to the use of two or more conventional anti-seizure medication (ASMs), poses a significant therapeutic challenge. In recent years, cannabidiol (CBD), a non-psychoactive compound derived from Cannabis sativa, has emerged as a promising adjunctive therapy for specific, severe epilepsy syndromes. The approval of a highly purified 99% CBD oral solution (Epidiolex®) has facilitated its integration into clinical practice. However, its effective and safe use requires a nuanced understanding of several practical considerations. This narrative review synthesizes current evidence on the practical aspects of prescribing and administering highly purified CBD oral solution in patients with drug-resistant epilepsy (DRE). I address evidence-based dosing strategies, relevant drug-drug interactions, the profile of adverse-drug reactions (ADRs) and their management, and the critical importance of gradual dose titration. A comprehensive literature search was conducted to identify relevant clinical trials, systematic reviews, observational studies, real-world evidence, and other pertinent publications. A “start low, go slow” dosing approach is essential to mitigate ADRs, which are generally mild to moderate but may include somnolence, decreased appetite, diarrhea, and, most notably, elevated liver transaminases, particularly with concurrent valproate use. Significant pharmacokinetic interactions, especially with clobazam, require careful monitoring and potential dose adjustments of concomitant ASMs. This review offers a consolidated overview of the practical considerations for CBD therapy, aiming to support clinicians in optimizing treatment outcomes for patients with DRE while ensuring patient safety.